2004
DOI: 10.1590/s0103-84782004000600035
|View full text |Cite
|
Sign up to set email alerts
|

Biodigestão anaeróbia de dejetos de bovinos leiteiros submetidos a diferentes tempos de retenção hidráulica

Abstract: RESUMO Utilizando

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 5 publications
2
18
1
23
Order By: Relevance
“…The hydraulic retention time of 15 days employed in our study was lower than that reported in Brazil by Amaral et al (2004). In both studies, survival of parasites was evident, indicating that retention periods between 15 and 20 days do not reduce worm viability, and suggest the need for periods longer than 30 days to inactivate 80% of the eggs (FURLONG;PADILHA, 1996).…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The hydraulic retention time of 15 days employed in our study was lower than that reported in Brazil by Amaral et al (2004). In both studies, survival of parasites was evident, indicating that retention periods between 15 and 20 days do not reduce worm viability, and suggest the need for periods longer than 30 days to inactivate 80% of the eggs (FURLONG;PADILHA, 1996).…”
Section: Resultscontrasting
confidence: 52%
“…In this context, L3 larvae of Haemonchus spp., Cooperia spp., and Oesophagostomum spp. may survive for 35 to 40 days in effluents (AMARAL et al, 2004;MENTZ et al, 2004) and eggs of Ascaris spp., Toxocara spp., Truchuris spp., and Hymenolepis spp. remain viable for longer periods under laboratory conditions (O'DONNELL et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Os valores de NMP de coliformes fecais e totais no efluente observados neste trabalho, foram considerados dentro da normalidade observando-se os resultados de Amaral et al (2004) (Mentz et al, 2004a).…”
Section: Resultsunclassified
“…Para Amaral et al (2004), o processo de biodigestão promoveu a redução da contagem de ovos de helmintos em dejetos bovinos; entretanto, 40 dias de retenção foram insuficientes para impedir a sobrevivência das larvas, após a coprocultura do efluente; para o trematódeo Fasciola hepatica dos bovinos, o período de retenção do material em biodigestão anaeróbia não deve ser inferior a 42 dias, antes do seu retorno ao ambiente (Mentz et al, 2004b).…”
Section: Resultsunclassified
“…Existe uma terceira vertente importante relacionada ao uso do efluente para melhorar a fertilidade de solo e, com isso, aumentar a sustentabilidade do sistema produtivo. 5 Sistemas biodigestores, ainda no país, são apresentados na literatura visando o tratamento de resíduos de processamento de mandioca, 6 estercos bovino e suíno, 7,8 com excelentes resultados do ponto de vista sanitário e ambiental.…”
Section: Introductionunclassified